PENGARUH KETERLIBATAN PEMAKAI TERHADAP KINERJA SIA DENGAN PROGRAM PELATIHAN PEMAKAI SIA SEBAGAI VARIABEL MODERASI PADA KSP DI DESA SIBANGKAJA - Putu Diah Asrida; Ni Putu Candri Artini (Widyadari : Jurnal Pendidikan, 2021)
This study aims to determine user involvement on SIA performance in savings and loan cooperatives in Sibangkaja Village and determine the effect of SIA user training programs on moderating or strengthening the effect of user involvement on SIA performance in savings and loan cooperatives in Sibangkaja Village. The results of the study show that (1) the user involvement variable has an effect on the performance of the AIS. The calculation results obtained a regression coefficient of 2.830, the t-count value is 2.354 and the sig value is 0.021 <0.05, so user involvement partially affects the performance of AIS. (2) The interaction variable of user involvement with the SIA training program on the performance of SIA, gives the calculation results obtained a regression coefficient of -0.112, the t-count value is -2.193 and the sig value is 0.032 <0.05. So it can be concluded that the second hypothesis, namely the interaction of user involvement with the SIA training program, has an effect on the performance of the SIA. The amount of Adjusted R Square is 0.420, which means that 42% of the variation in SIA performance is influenced by user involvement, while the Adjusted R Square value based on variations in SIA performance which is influenced by the interaction of user involvement with the SIA training program has increased to 0.767, which means 76.7 %, while the remaining 23.3% is influenced by other factors outside of this study.